2011
DOI: 10.1021/jp107630q
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Small Base Molecules and Tetrahedral/Cubane-Like Clusters of Group V Atoms in the Boron Buckyball: A Density Functional Theory Study

Abstract: A density functional theory study of small base molecules and tetrahedral and cubane-like group V clusters encapsulated in B(80) shows that the boron buckyball is a hard acid and prefers hard bases like NH(3) or N(2)H(4) to form stable off-centered complexes. In contrast, tetrahedral and cubane-like clusters of this family are metastable in the cage. The most favorable clusters are the mixed tetrahedral and cubane clusters formed by nitrogen and phosphorus atoms such as P(2)N(2)@B(80), P(3)N@B(80), and P(4)N(4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 83 publications
3
22
0
Order By: Relevance
“…15 A recent study even claims that there may not be driving forces towards well defined structures, and that the potential energy surface of the larger boron clusters resembles a glasslike landscape. 16,17 In view of its high symmetry and its paradigmatic electronic structure, the boron buckyball continues to attract detailed theoretical studies of its chemical and physical properties, [18][19][20][21][22] as was the case for its famous carbon congener in previous decades. In the present work we calculate the magnetically induced ring currents in the boron buckyball, both in I h and T h symmetries, and compare them with those of C 60 .…”
Section: Introductionmentioning
confidence: 99%
“…15 A recent study even claims that there may not be driving forces towards well defined structures, and that the potential energy surface of the larger boron clusters resembles a glasslike landscape. 16,17 In view of its high symmetry and its paradigmatic electronic structure, the boron buckyball continues to attract detailed theoretical studies of its chemical and physical properties, [18][19][20][21][22] as was the case for its famous carbon congener in previous decades. In the present work we calculate the magnetically induced ring currents in the boron buckyball, both in I h and T h symmetries, and compare them with those of C 60 .…”
Section: Introductionmentioning
confidence: 99%
“…By the way, it should be mentioned that the relative stability of various isomers of carborane C 2 B n −2 H n (5 ≤ n ≤ 7) had ever been studied by Williams, Jemmis, Gimarc, and McKee . The geometries of normalBnnormalHn2 (5 ≤ n ≤ 7), 1,5‐C 2 B 3 H 5 , 1,6‐C 2 B 4 H 6 , and 1,7‐C 2 B 5 H 7 displayed in Figure are optimized and confirmed by vibration frequency analysis at B3LYP/def2‐TZVPP level with Gaussian 09 package, where the B3LYP/def2‐TZVPP method is always used as structure optimization method for boranes and borane analogs . Based on the geometry optimization results, the precise frontier orbital energy levels E SCF (∞) are extrapolated according to Eq.…”
Section: The Calculated Results Of Normalbnnormalhn2− and C2bn−2hn (mentioning
confidence: 76%
“…Since the discovery of boron nanotubes and the tendency of small boron clusters to keep planar or quasi-planar shapes, it has been believed that large boron clusters may have fullerene-like structures. Several theoretical studies [16,[19][20][21][22][23][24][25][26][27][38][39][40][41][42][43][44][45][46] have been reported that characterise the leapfrog boron fullerene B 80 with all 20 hexagons capped. Wang [19] mentioned that the displacement of hexagon caps towards pentagons leads to more stable boron clusters, but could not give any reliable explanation for the relative stability of these structures.…”
Section: B 80 Clustersmentioning
confidence: 99%
“…The authors thank the KULeuven Research Council and the Flemish Science Fund (FWO-Vlaanderen) for financial support and P. W. Fowler for sending us the coordinates of the C 24 Keywords: boron · cage compounds · cluster compounds · density functional calculations · isomers…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation